Marketing management functions of construction companies: Evidence from Turkish contractors - Polat, Gul; Donmez, Umit (Journal of Civil Engineering and Management, 2010)
Globalization, the restructuring of the world economy, changes experienced in project financing and delivery systems, the pervasive utilization of information and communication technologies (ICT), and the intensity of the competition prevailing in the market compel contractors to rethink the competitive forces and client expectations, which in turn necessitate a well planned marketing orientation for business planning. The Turkish construction industry is not different from the global construction industry in the context of intense competitiveness as Turkish contractors do not only undertake projects in the domestic market but also in foreign markets including the Commonwealth of Independent States, Africa, Middle East, Europe, Asia, etc. They also often face intense competition from local and foreign companies such as U.S., Chinese, Japanese, French, Spanish, German, U.K., and Korean contractors. Given the intense competition, effective marketing of their services is imperative for Turkish contractors in achieving competitive advantage. This study explores the marketing management functions of Turkish construction companies and the extent to which they carry out traditional marketing practices via a questionnaire survey of 71 Turkish contractors. The survey results revealed that Turkish contractors made use of marketing management functions to some extent, yet responding contractors did not attach adequate importance to differentiating their products/services from the products/services offered by their competitors. Since achieving client satisfaction by means of product and/or service differentiation is the ultimate goal, Turkish contractors should carry out all of the traditional marketing practices in order to differentiate themselves in the market, and thereby create competitive advantage. First Published Online: 24 Jun 2011